2021
DOI: 10.1371/journal.pone.0251708
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and preventive practice towards COVID-19 and associated factors among outpatient service visitors at Debre Markos compressive specialized hospital, north-west Ethiopia, 2020

Abstract: Background COVID-19 is an emerging infectious disease which is a major public health problem worldwide. Given the serious threats imposed by COVID-19 and the absence of vaccines until August 2020, preventive measures play an essential role in reducing infection rates and controlling its spread. This shows the necessity of public adherence for preventive and control measures, which is affected by their knowledge, attitudes, and practices. Objective This study aimed to determine knowledge, attitude, and practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 19 publications
4
46
4
2
Order By: Relevance
“…In Saudi Arabia, the HCWs are expected to have excellent/good knowledge (≥ 80%) in infection control and other common public health activities as they are the first in line in managing the BMW. Our categorization is in accordance with the original Bloom’s cut-off point for assessing KAP and is supported by previous studies conducted among healthcare workers in the KSA and other parts of the world ( Mohammed Basheeruddin Asdaq et al, 2021 ; Feleke, Wale & Yirsaw, 2021 ; Abalkhail et al, 2021 ). Additionally, we combined low and medium scores as a single category for further analysis, and previous studies among the HCWs strongly support our categorization ( Abalkhail et al, 2021 ; Thirunavukkarasu et al, 2021 ; Ukwenya et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
“…In Saudi Arabia, the HCWs are expected to have excellent/good knowledge (≥ 80%) in infection control and other common public health activities as they are the first in line in managing the BMW. Our categorization is in accordance with the original Bloom’s cut-off point for assessing KAP and is supported by previous studies conducted among healthcare workers in the KSA and other parts of the world ( Mohammed Basheeruddin Asdaq et al, 2021 ; Feleke, Wale & Yirsaw, 2021 ; Abalkhail et al, 2021 ). Additionally, we combined low and medium scores as a single category for further analysis, and previous studies among the HCWs strongly support our categorization ( Abalkhail et al, 2021 ; Thirunavukkarasu et al, 2021 ; Ukwenya et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
“…Our study found a low prevalence of 14.8% of participants' knowledge of COVID-19 prevention measures. This prevalence is lower compared to that reported in Ethiopia 27.1% (Feleke et al, 2021), Uganda 16.1% (Ssebuufu et al, 2020), and Malaysia 19.5% (Azlan et al, 2020). The lower knowledge level could be due to differences in socioeconomic status and education level of the participants.…”
Section: Discussioncontrasting
confidence: 63%
“…Meanwhile, the attitude score obtained in the present study was greater than that of undergraduates in China (85%) and Indonesia (91%) [ 12 , 17 ]. Based on Bloom’s cut-off (Good score: 80–100%, moderate score: 60–79%, and poor score: 0–59%) classification [ 18 ], the respondents in this study had good attitudes but moderate knowledge and practice levels towards COVID-19. As the adoption of COVID-19 preventative measures is strongly influenced by one’s knowledge [ 19 ], the government, health, and university authorities need to tailor a standardized nationwide COVID-19 education program to university students before going all out on reimplementing face-to-face teaching and learning.…”
Section: Discussionmentioning
confidence: 99%